USING SONGS THROUGH LINGOCLIP APPLICATION IN TEACHING VOCABULARY AT SMAS KARYA BAKTI - Iskandar, Risda Alena; Helmie, Jauhar; Saepuloh, Asep (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2024)
Vocabulary is the most important for students to learn and possess. Even though vocabulary is the basis of all English language skills, there are still students who find it difficult to have a variety of English vocabulary. The aims of this research are to find out the results of the analysis of the implementation of the vocabulary teaching method using songs and the LingoClip application as media, as well as to find out the advantages and disadvantages of this method. This research uses descriptive qualitative by using questionnaires and interviews. The results of this research showed that: (1) 44% of students felt interested in the implementation of this method, 88% of students felt helped by the effectiveness of this method, 92% of students found their ability to learn vocabulary increased, and 96% of students preferred this method (2) students get more advantages than disadvantages, including; this method is simpler for students, adds vocabulary skills, students are motivated to learn English, and this method is a method that is not boring for students (3) the disadvantages of this method that are felt by some students are the need for an internet network that must be stable, also suggestions from students are the need for a device that supports running this application.Keywords: Vocabulary, Songs, Language, Skill, LingoClip Application, Teaching Method.